Expression and Distribution of Neuropeptide-Expressing Cells Throughout the Rodent Paraventricular Nucleus of the Thalamus - Curtis, Genevieve R.; Oakes, Kathleen; Barson, Jessica R. (Frontiers in Behavioral Neuroscience, 2021)
The paraventricular nucleus of the thalamus (PVT) has been shown to make significant contributions to affective and motivated behavior, but a comprehensive description of the neurochemicals expressed in the cells of this brain region has never been presented. While the PVT is believed to be composed of projection neurons that primarily use as their neurotransmitter the excitatory amino acid, glutamate, several neuropeptides have also been described in this brain region. In this review, we combine published literature with our own observations from the Allen Brain Atlas to describe in detail the expression and distribution of neuropeptides in cells throughout the mouse and rat PVT, with a special focus on neuropeptides known to be involved in behavior. Several themes emerge from this investigation. First, while the majority of neuropeptides are expressed across the antero-posterior axis of the PVT, they generally exist in a gradient, in which expression is most dense but not exclusive in either the anterior or posterior PVT, although other neuropeptides display somewhat more equal expression in the anterior and posterior PVT but have reduced expression in the middle PVT. Second, we find overall that neuropeptides involved in arousal are more highly expressed in the anterior PVT; those involved in depression-like behavior are more highly expressed in the posterior PVT; and those involved in reward are more highly expressed in the medial PVT; while those involved in the intake of food and drugs of abuse are distributed throughout the PVT. Third, the pattern and content of neuropeptide expression in mice and rats appears not to be identical, and many neuropeptides found in the mouse PVT have not yet been demonstrated in the rat. Thus, while significantly more work is required to uncover the expression patterns and specific roles of individual neuropeptides in the PVT, the evidence thus far supports the existence of a diverse yet highly organized system of neuropeptides in this nucleus. Determined in part by their location within the PVT and their network of projections, the function of the neuropeptides in this system likely involves intricate coordination to influence both affective and motivated behavior.